Detection and mitigation of antibiotic residues in poultry products and byproducts - Islam, Md Shafiqul; Sachi, Sabbya; Dash, Sharmy; Islam , Md Shakil (Asian-Australasian Journal of Food Safety and Security, 2023)
Majority of the people in Bangladesh are still not aware about the health hazards of antibiotic residues. In this research, farmer’s awareness has been investigated by a questionnaire in different poultry farms, retail sellers and poultry markets and spread out the knowledge of public health hazards of antibiotics residues. Poultry farmers were found well educated about health hazards of antibiotic residues and aware about the judicial use of antibiotics before selling the poultry for human consumptions. During this survey, sufficient samples (thigh muscle, breast muscle, liver etc., n=100) were collected from different poultry farms, retail sellers and poultry markets. Randomly 50 livers, 50 thigh muscle and 50 breast muscle samples respectively were evaluated by TLC analysis. Out of 50 samples for each 2 liver, 2 breast muscle and 2 thigh muscle samples were found positive for Amoxicillin antibiotic; 5 liver, 3 breast muscle and 3 thigh muscle samples were found positive for Ciprofloxacin; 3 liver, 3 breast muscle and 3 thigh muscle samples were found positive for Cefalexin; 2 liver, 2 breast muscle and 2 thigh muscle samples were found positive for Enrofloxacin; 4 liver, 2 breast muscle and 2 thigh muscle samples were found positive for Oxytetracycline. Gentamicin and Neomycin were found negative for any samples. Further investigation was done in indoor discriminate and indiscriminate use of antibiotics (Cefalexin) in broilers. Indoor experiment was investigated in poultry chicks. Day old chicks were collected and reared up to 30 days. On day 14th, the chicks were randomly divided into three groups namely control group (n=10), discriminate antibiotic group (n=10) and indiscriminate antibiotic group (n=10). Discriminate antibiotic group was treated with antibiotics (Cefalexin) for one week followed by withdrawal period for one week, whereas; indiscriminate antibiotic group was treated with antibiotic (Cefalexin) for two weeks until the day of sacrifice. Liver, thigh muscle and breast muscle samples were collected and evaluated by TLC method. Control and discriminate antibiotics birds were found negative for any antibiotics residues. On the other hand, ten liver samples, eight thigh muscles and eight breast muscles were found positive for Cefalexin in indiscriminate group. Indiscriminate uses of antibiotic indicated that antibiotic residue mitigation for human safe meat production depends on withdrawal period and farmers awareness. Therefore, poultry treated with antibiotics are required for specific withdrawal period until all residues are depleted to safe levels before human consumption. Asian Australas. J. Food Saf. Secur. 2023, 7 (1), 33-39